Non-Cirrhotic Portal Hypertension: An Update of Diagnosis and Management - Zulkifly, Steven; Hasan, Irsan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
Portal hypertension is not the only caused by liver cirrhosis. Non-cirrhotic portal hypertension (NCPH) is characterized by elevated portal pressure in the absence of cirrhosis and is often underdiagnosed in daily clinical practice. The clinical manifestations of NCPH are similar to liver cirrhosis. The diagnosis of NCPH is still challenging due to the various underlying etiologies and often require either non-invasive or invasive examination. Laboratory examination, abdominal ultrasound, endoscopic procedure, hepatic venous gradient measurement, and liver biopsy have role in diagnosis of NCPH. The principle management of NCPH is to treat portal hypertension and its complications, such as prophylaxis and acute management of variceal bleeding, anticoagulants, surgery, splenectomy, and liver transplantation.